Systolic blood pressure values, Vascular Doppler Pulsed Method, in conscious healty dogs (Veterinary Science, 2017)
Blood pressure is a variable systemic is governing the tissues blood perfusion. Their values, in healthy dogs and cats, are influenced by physiological variables present at moment the study as heart rate, systolic discharge and peripheral arterial resistance. The aim of this study was to evaluate the systolic blood pressure in healthy dogs by technique Vascular Doppler with order to expand their knowledge in companion animals. The study population consisted of 96 dogs: 56 purebred and 40 mix-breed; 53 females and 43 males; 67 not castrated and 29 castrated; 33 small sizes, 30 average sizes and 33 large sizes. The average weight was 20.13 kg (range 2.95 kg - 48.3 kg) and the average age was 5 years (range 1-16 years). All animals included in the study underwent clinical examination, radiological, electrocardiography, echocardiography, hematologic and biochemical, to determine their health status. Samples with signs of disease at the preliminary examination were ruled. The average systolic blood pressure found 145.50 ± 21.7 mm Hg, over the range 83.14 - 184.28 mmHg. Values did not differ significantly between consecutive registers. The values found in this study are within the normal range for healthy dogs established by other researchers.
Keywords: Healthy canines; Blood pressure